Relationship of ABO Blood Groups with Body Mass Index (Medico Legal Update, 2020)
Background: Obesity predisposing factors have been raised as a major concern of researchers due to theconsequences of obesity on health such as diabetes, hypertension, and depression, ABO blood groups linkedto many diseases, so may affect directly or indirectly on the incidence of obesity.Objectives: The study aims to find out the association of ABO blood groups with body mass index.Method: A cross-sectional study was conducted with a non-probability purposive sample of 2604 youngadulthood age (18-25 years) that does not have previous surgery or chronic diseases through an electronicquestionnaire in Iraq. A statistical package for social science (SPSS) program, version 24 was used fordescriptive and inferential statistics.Results: Blood group O was a common frequency in people with increased body mass index, so highstatistically significant association recorded (p ? 0.001). In addition, most of the subject (86.6%) havepositive rhesus (Rh +).Conclusions: People with blood group O and positive RH were most vulnerable to increase their body massindex.